Classical Hinduism Documenta Missionalia - Podgorski, Frank (Journal of Dharma, 1983)
Mariasusai Dhavamony, S. J. Classical Hinduism Documenta Missionalia 15. Roma : Gregoriano, 1982. vii +525 pp. 31.00